2016
DOI: 10.3847/2041-8205/832/1/l5
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Background at High Redshifts From Pop Iii Remnants: Results From Pop Iii Star Formation Rates in the Renaissance Simulations

Abstract: Due to their long mean free paths, X-rays are expected to have global impacts on the properties of the intergalactic medium (IGM) by their large scale heating and ionizing processes. At high redshifts, X-rays from Population (Pop) III binaries might have important effects on cosmic reionization and the Lyα forest. As a continuation of our previous work on Pop III binary X-rays , we use the Pop III distribution and evolution from the Renaissance Simulations, a suite of self-consistent cosmological radiation hyd… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 64 publications
(113 reference statements)
4
13
0
Order By: Relevance
“…We predict a Pop III SFRD that is about 40− 100 times higher than that in the "rare peak" simulation by Xu et al (2013Xu et al ( , 2016b, and closer to the level obtained by Chon et al (2016) (assuming h = 0.73, see their figure 2). If compared with the "rare peak" simulation presented by Xu et al (2013Xu et al ( , 2016b, the higher SFRD that we find in our model reflects the conditions in the highly biased region that we are considering. If we estimate the over-density of our comoving vol-ume (50 Mpc 3 ) following the definition of Xu et al (2016a), < δ >=< ρ > /(Ω M ρ cr ) − 1, we find < δ >∼ 5, a factor of ∼ 7 higher than that of the "rare peak" simulation (< δ >∼ 0.68, see e.g.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We predict a Pop III SFRD that is about 40− 100 times higher than that in the "rare peak" simulation by Xu et al (2013Xu et al ( , 2016b, and closer to the level obtained by Chon et al (2016) (assuming h = 0.73, see their figure 2). If compared with the "rare peak" simulation presented by Xu et al (2013Xu et al ( , 2016b, the higher SFRD that we find in our model reflects the conditions in the highly biased region that we are considering. If we estimate the over-density of our comoving vol-ume (50 Mpc 3 ) following the definition of Xu et al (2016a), < δ >=< ρ > /(Ω M ρ cr ) − 1, we find < δ >∼ 5, a factor of ∼ 7 higher than that of the "rare peak" simulation (< δ >∼ 0.68, see e.g.…”
Section: Discussionsupporting
confidence: 81%
“…With the above caveat in mind, we have compared our results with the recent enzo Renaissance simulation presented by Xu et al (2013Xu et al ( , 2016a ("rare peak" case) and with the Gadget-2 simulation by Chon et al (2016). We predict a Pop III SFRD that is about 40− 100 times higher than that in the "rare peak" simulation by Xu et al (2013Xu et al ( , 2016b, and closer to the level obtained by Chon et al (2016) (assuming h = 0.73, see their figure 2). If compared with the "rare peak" simulation presented by Xu et al (2013Xu et al ( , 2016b, the higher SFRD that we find in our model reflects the conditions in the highly biased region that we are considering.…”
Section: Discussionsupporting
confidence: 67%
“…Possibilities include substantially more efficient HMXB formation than in the local Universe, a different wind environment or alternative wind production mechanisms, or additional sources of heating altogether. Other heating sources that have been considered include high mass X-ray binaries formed from Population III stars (Xu et al 2016) and an early population of mini-QSOs (Kuhlen et al 2006) or galaxies harbouring moderately massive black holes (Pacucci et al 2015). An initial mass function tilted towards massive Pop III stars could also lead to greater heating from pair-instability supernovae remnants.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that this high-z component could originate from accretion powered sources during the epoch of reionization (EoR), such as XRBs (Fragos et al 2013a,b;Xu et al 2016), and/or AGNs (Dijkstra et al 2004; Salvaterra et al 2005Salvaterra et al , 2007. Although they are also expected to contribute to the CXB, it is not possible to separate such components directly from the CXB measurements due to the lack of redshift information.…”
Section: Introductionmentioning
confidence: 99%